Impact of International Trade and Globalization on Financial Markets: A Case of Pakistan - Kiani, Memoona Manzoor; Raisani, Shain Taj; Nabeel, Muhammad; Khan, Shahan Zeb; Lodhi, Kashif (Bulletin of Business and Economics (BBE), 2023)
This study investigates the intricate relationship between international trade, globalization, and Pakistan’s financial markets through quantitative analysis. Using regression, correlation, time-series, and comparative methodologies, data from 2018 to 2022 was analyzed. Findings indicate a direct correlation between higher trade volumes and improved stock market performance, while a rising globalization index aligns with increased capital inflows. Exchange rate fluctuations reflect the currency’s sensitivity to global economic shifts. Comparative analysis with regional counterparts highlights both aligned and divergent financial market trends. Moreover, a sensitivity analysis emphasizes the potential impact of Foreign Direct Investment (FDI) on stock market indices. These insights underscore the importance of trade policies, global integration, and FDI in shaping Pakistan’s financial market dynamics within the evolving global economic landscape.